Epicutaneous immunotherapy for peanut allergy treatment in pediatrics: A literature review - Fadya, Vannisa; Safira, Siti Sarah; Nabila, Amira Qisthy; Yufika, Amanda (Medical Faculty of Brawijaya University, Indonesia, 2025)
Peanut allergy in children is a growing public health concern that significantly affects patients' quality of life. Although oral immunotherapy (OIT) has shown effectiveness in desensitizing allergic reactions, it is associated with a threefold increased risk of anaphylaxis compared to strict avoidance. As an alternative, epicutaneous immunotherapy (EPIT) has emerged as a promising therapy due to its favorable safety profile, ease of administration, and non-invasive nature. However, despite increasing interest in EPIT, there is still limited evidence assessing its efficacy and safety in pediatric populations. This literature review aims to summarize current findings on the mechanism of desensitization, clinical efficacy, safety, and impact on quality of life associated with EPIT in managing peanut allergy in children. Relevant articles were identified through database searches in PubMed, Cochrane, Science Direct, Scopus, and Google Scholar using Medical Subject Headings (MeSH) and keyword combinations such as